Prevalence of Small Intestinal Bacterial Overgrowth Syndrome in Patients with Irritable Bowel Syndrome who Have Suffered COVID-19 - A. V. Nalyotov; N. P. Guz (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To study the prevalence of the small intestinal bacterial overgrowth syndrome in patients with irritable bowel syndrome with diarrhea who have had COVID-19 infection.Materials and methods. 60 patients with irritable bowel syndrome with diarrhea were examined. In 30 patients, irritable bowel syndrome was diagnosed after COVID-19 infection (main group). The comparison group consisted of 30 patients with classical stress-induced irritable bowel syndrome. The small intestinal bacterial overgrowth syndrome was diagnosed using a hydrogen breath test with lactulose loading in all patients.Results. In main group the small intestinal bacterial overgrowth syndrome was diagnosed in 93.3 % patients, which was statistically significantly higher (p < 0.01) relative to the comparison group — 60.0 % patientsConclusion. Irritable bowel syndrome in patients who have undergone COVID-19 occurs against the background of the small intestinal bacterial overgrowth syndrome development.